Coffeehouse Curiosities: Materiality and Musealization Strategies in The Athenian Mercury - Jasenowski, Jaroslaw (Journal for Eighteenth-Century Studies, 2024)
Based on the epistolary interaction with readers, John Dunton's Athenian Mercury (1691–97) provided a platform for the discussion and dissemination of knowledge drawn from diverse fields. Plagued by doubts about its reliability, the periodical constantly had to (re-)assert its credibility. One of the strategies the Mercury employed was to emphasize the physicality of objects via text, practising a performance of materiality. Taking the letter-as-object as its starting point, this article argues that materiality played a crucial role in not only the representation but also the active production of truthfulness. Examining how Dunton's periodical leveraged notions of the coffeehouse as an exhibition space, this article explores how the Mercury drew on musealization strategies to represent material objects to underline their existence and its own credibility. Interpellating readers as virtuosi, the Athenian Society staged the coffeehouse and even itself as a walk-in curiosity cabinet, turning letters into matter and fiction into fact.
CRIS-Team Scopus Importer:2024-03-15
Keywords: coffeehouse culture; curiosity culture; epistolarity; factuality; fictionality; material culture; truth discourses; veracity; virtuoso culture

Dragging out the Truth: Restoration Periodicals and the Textual Creation of Gendered Identities - Bayer, Gerd; Jasenowski, Jaroslaw (Revista Canaria de Estudios Ingleses, 2019)

Introduction: Restoration Epistolarity - Bayer, Gerd; Jasenowski, Jaroslaw (Journal for Eighteenth-Century Studies, 2024)
The early modern age witnessed a number of revolutionary changes in the ways people communicated with each other. Within the shifting balances between oral and print cultures following upon Gutenberg's invention of the printing press, epistolarity played a crucial role in how written language was perceived as a source of reliable information. The highly dynamic cultural environment of Restoration England, existing as it did in various forms of intellectual exchange with other European and international spheres, brought forth a sizeable increase in various forms of literary practice.<br

Performing Factuality in John Dunton’s Athenian Cosmos: The Rites of Truth - Jasenowski, Jaroslaw (Palgrave Macmillan, 2024)
Starting from the fundamental epistemological shifts characterising the seventeenth century, this book explores the re-conceptualization of the notion of truth and asks how factuality, along with other truth-carrying discourses, was appropriated by a range of texts to generate credibility. Tracing the numerous ways in which authors such as John Dunton, Charles Gildon, François Perreaud, Thomas Brown, or Joseph Addison and Richard Steele deliberately toyed with the truth effects generated by their participation in discourses such as proto-science, medicine, philosophy, law and religion, this monograph argues that truth is not a monolithic constant. Performing Factuality proposes that truth is protean, ever- emerging from a simultaneously conventionalised yet constantly mutating set of practices, something which not simply is but something which is actively done. This performative dimension finds one of its most powerful examples in the case of Dunton and his handful of collaborators working on the Athenian Mercury, which set the tone in periodical publication for decades if not centuries to come.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 17th Century Literature; Athenian Cosmos; Athenian Society; Coffeehouse Culture; Daniel Defoe; John Dunton; Periodical Publication; Restoration

Restoration Epistolarity - Bayer, Gerd; Jasenowski, Jaroslaw (Wiley, 2024)